PEMISAHAN HARTA BERSAMA PADA POLIGAMI DIBAWAH TANGAN (STUDI KASUS DI DESA TEBING LESTARI KABUPATEN KAMPAR) - Elpiya '; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Marriage in Indonesia under the Act is based on monogamous marriage but not limiting. Marriages taking place not only marriage one husband with one wife, although in principle it was. Problems will occur when there is no division of joint property. The authors found that polygamy divorces occurred in the village of Cliffs Lestari no division of community property between husband and ex-wife of former poligaminya both religious law and customary law, so the former wife of polygamy did not get a part of the joint property. The second is based on the author intends to examine the differences in the form of a thesis with the title